2009
DOI: 10.1111/j.1365-2427.2009.02234.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between structure and function in streams contrasting in temperature

Abstract: Summary 1. We studied 10 first‐order Icelandic streams differing in geothermal influence in separate catchments. Summer temperature (August–September) ranged between 6 and 23 °C. 2. Macroinvertebrate evenness and species overlap decreased significantly with temperature whereas taxon richness showed no response. In total, 35 macroinvertebrate species were found with Chironomidae the dominant taxonomic group. Macroinvertebrate density increased significantly with temperature. Dominant species in the warm streams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
269
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(289 citation statements)
references
References 65 publications
18
269
1
1
Order By: Relevance
“…This stimulation was expected since the activities of most temperate fungi and invertebrate species are stimulated by warming within the temperature range observed (Azevedo-Pereira et al 2006;Dang et al 2009;Ferreira and Chauvet 2011a, b). This stimulation is also in agreement with metabolic theory (Brown et al 2004) and with studies where litter was incubated along natural thermal gradients (Irons et al 1994;Fabre and Chauvet 1998;Swan and Palmer 2004;Friberg et al 2009;Boyero et al 2011b). Although an increase in water temperature by 10°C is over that expected for temperate woodland streams solely due to global warming (IPCC (Intergovernmental Panel on Climate Change) 2007; Morrill et al 2005), increases of this magnitude may occur under global-warming scenarios that include removal of riparian vegetation, water abstraction, or warm-water discharge from power plants (Poff and Mathews 1986;Stefan and Sinokrot 1993).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This stimulation was expected since the activities of most temperate fungi and invertebrate species are stimulated by warming within the temperature range observed (Azevedo-Pereira et al 2006;Dang et al 2009;Ferreira and Chauvet 2011a, b). This stimulation is also in agreement with metabolic theory (Brown et al 2004) and with studies where litter was incubated along natural thermal gradients (Irons et al 1994;Fabre and Chauvet 1998;Swan and Palmer 2004;Friberg et al 2009;Boyero et al 2011b). Although an increase in water temperature by 10°C is over that expected for temperate woodland streams solely due to global warming (IPCC (Intergovernmental Panel on Climate Change) 2007; Morrill et al 2005), increases of this magnitude may occur under global-warming scenarios that include removal of riparian vegetation, water abstraction, or warm-water discharge from power plants (Poff and Mathews 1986;Stefan and Sinokrot 1993).…”
Section: Discussionsupporting
confidence: 69%
“…Water temperature of streams and rivers is expected to follow this increase by rising 0.6-1.0°C for each degree of increase in air temperature (Morrill et al 2005). This increase in water temperature might have strong effects on biotic communities and ecological processes (Hogg and Williams 1996;Friberg et al 2009), since species distribution, phenology, and biological activities are temperature-dependent (Parmesan and Yohe 2003;Brown et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the existing research results showed that nutrient availability (Larned, 2010;Mulholland and Webster, 2010;Guariento et al, 2011;Drake et al, 2012), temperature (Friberg et al, 2009;Demars et al, 2011;Gudmundsdottir et al, 2011) and light (Fanta et al, 2010;Hill et al, 2011;Ohta et al, 2011;Stephens et al, 2012) were the factors restricting the abundance of stream periphyton. With respect to nutrient availability, no unified conclusions are recognized to date, although much research has been conducted in the past.…”
Section: Relationships Between Environmental Variables and Periphytonmentioning
confidence: 99%